Increasing Antioxidant Activity and Protein Digestibility in Phaseolus vulgaris and Avena sativa by Fermentation with the Pleurotus ostreatus Fungus - Espinosa Páez, Edith; Alanís Guzmán, María Guadalupe de Jesús; Hernández Luna, Carlos Eduardo; Báez González, Juan Gabriel; Amaya Guerra, Carlos Abel; Andrés Grau, Ana M. (Molecular Diversity Preservation International, 2017)
Abstract: TheaimoftheresearchwastodeterminetheimpactoffermentationwithPleurotusostreatus on kidney beans, black beans, and oats. The results indicate that the fungus has a positive effect on the substrates when compared to the controls. The antioxidant activity (39.5% on kidney beans and 225% on oats in relation to the controls) and content of total polyphenols (kidney beans three times higher regarding the controls) increased signiﬁcantly by the presence of the fungus mycelium, even after simulated digestion. There was a signiﬁcant increase in protein digestibility (from 39.99 to 48.13% in black beans, 44.06 to 69.01% in kidney beans, and 63.25 to 70.01% in oats) and a decrease of antinutrient tannins (from 65.21 to 22.07 mg in black beans, 35.54 to 23.37 in kidney beans, and 55.67 to 28.11 in oats) as well as an increase in the contents of some essential amino acids. Overall, this fermentation treatment with Pleurotus ostreatus improved the nutritional quality of cereals and legumes, making them potential ingredients for the elaboration and/or fortiﬁcation of foods for human nutrition. Keywords: Pleurotus ostreatus; antioxidant activity; polyphenols; digestibility; fermentation; cereals; legumes